AAA ELECTIVE TREATMENT INDICATION TACTICS IN EVAR ERA - Utíkal, Petr; Köcher, Martin; Koutná, Jiřina; Bachleda, Petr; Dráč, Petr; Černá, Marie; Buriánková, Eva (Biomedical papers, 2004)
The authors describe their indication tactics for AAA elective treatment. Based on one-month morbidity and mortality they evaluate the results obtained in the past six years and compare the methods of open surgery, endovascular repair and combined strategy in AAAs elective repair.
Keywords: Aneurysm/Aorta/Indications/Strategy/Surgery/Endovascular/Combined/Mortality/Morbidity